Designing Online Learning on Graphic Design Course During COVID-19 Pandemic - Tian, Mengfei; Huang, Zheng; Bu, Delu (International Journal of Art, Design, and Metaverse, 2023)
The COVID-19 pandemic forced most educational institutions to close learning to avoid spreading the virus. As a result, most of the student population in the world, from kindergarten to university level, have stopped their education temporarily. Many children, youth, and adults are not attending schools due to the increased spread of COVID-19, but learning should be conducted to enhance student competency. This paper aims to design the online learning method for graphic art courses conducted during the COVID-19 pandemic. The interaction between students and lecturers is conducted through zoom, and students do their assignments at home. Online learning findings showed that students performed at least as well as in conventional learning. The graphic design courses can be delivered online via video, Zoom meetings, or Google Meet. But, some problems still exist in online education, including infrastructure and teacher and student ability.